Jesus Christ message to all nations - Jeffs, Warren 1955- ([Fundamentalist Church of Jesus Christ of Latter-day Saints], 2013)
A compendium of prophecies attributed to Jesus Christ by Warren S. Jeffs during 2009-2013, principally at Palestine, Texas.